Pengembangan Media Permainan Ular Tangga Berbasis Kearifan Lokal di TK Babel Kids Pangkalpinang - Sari, Yurinda Witha; Risma, Risma (Fakultas Tarbiyah, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
This study aims to develop learning media for snakes and ladders game based on local wisdom of Bangka Belitung in BABEL KIDS Kindergarten Pangkalpinang. This research is the result of a study of the formulation of the problem, study is the result of a problem formulation study, namely the development of learning media for children's snake and ladder game based on local wisdom of Bangka Belitung in BABEL Kids Kindergarten Pangkalpinag. The purpose of this study was to determine the development of learning media for children's snake and ladder game based on local wisdom from Bangka Belitung at BABEL KIDS TK Pangkalpinang. The research method used Research and Development with the 5-stage ADDIE model, namely first, the results of the needs analysis of the BABEL KIDS Kindergarten require the development of learning media for the children's snake and ladder game because the media does not exist yet in BABEL KIDS Kindergarten. Second, the research design analysis had prepared the designs and compiled rules on how to play the snake and ladder game based on local wisdom from Bangka Belitung. Third, in the development stage, researchers distributed 2 questionnaires to media experts and material experts and were declared eligible for field trials. Fourth, the implementation analysis shows that the children succeeded in playing the snake and ladder game based on local wisdom from Bangka Belitung in accordance with the direction of the researcher. Fifth, the evaluation stage that the snake and ladder game based on local wisdom from Bangka Belitung developed by researchers has good results according to media experts and material experts.